1984
DOI: 10.1203/00006450-198412000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Ester and Triglyceride Metabolism in Intact Fibroblasts from Patients with Wolman's Disease and Cholesterol Ester Storage Disease

Abstract: ABSTRACT. Cholesterol ester and triglyceride metabolism was examined in intact fibroblast monolayers from normal individuals and patients with Wolman's disease and cholesterol ester storage disease. Cholesterol esters were introduced into cells by incubation in medium containing [3H]cholesteryl linoleate (CL) bound to human low density lipoprotein. Triglycerides were introduced by incubation with glycerol tri[l-'4CJoleate (trjolein) bound to hunian very low-density lipoprotein. Both types of mutant cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…This low level of residual catabolic activity is in agreement with the very low value for the acid lipase determined in vitro (c 5% of control) ( fig.2). It is also consistent with the values reported by Brown et al [24] and Goldstein and coworkers [25] for degradation of cholesteryl esters, but significantly lower than that determined by Burton et al [26] who probably overestimated the apparent residual activity because of the retroendocytosis process [5] occurring at the beginning of the chase. Therefore, the severe catabolic block in Wolman fibroblasts demonstrates that triacylglycerols stored in lysosomes cannot reach, to an appreciable extent, the cytoplasmic compartment where endogenously biosynthesized triacylglycer01s are degraded at the normal rate (as shown by studying endogenous triacylglycerol catabolism).…”
Section: Discussionsupporting
confidence: 82%
“…This low level of residual catabolic activity is in agreement with the very low value for the acid lipase determined in vitro (c 5% of control) ( fig.2). It is also consistent with the values reported by Brown et al [24] and Goldstein and coworkers [25] for degradation of cholesteryl esters, but significantly lower than that determined by Burton et al [26] who probably overestimated the apparent residual activity because of the retroendocytosis process [5] occurring at the beginning of the chase. Therefore, the severe catabolic block in Wolman fibroblasts demonstrates that triacylglycerols stored in lysosomes cannot reach, to an appreciable extent, the cytoplasmic compartment where endogenously biosynthesized triacylglycer01s are degraded at the normal rate (as shown by studying endogenous triacylglycerol catabolism).…”
Section: Discussionsupporting
confidence: 82%
“…20 In addition, Burton et al 21 reported the existence of a non-lysosomal hydrolysis pathway for cholesterol esters or triglycerides, in which neutral cholesterol ester hydrolase participates. Hence, two forms of hydrolysis of cholesterol esters from LDL in the liver have been identi®ed and attention has been paid to the relationship between the fatty acid composition of accumulated cholesterol esters and other lipids in the liver and the fatty acid composition of serum LDL.…”
Section: Discussionmentioning
confidence: 99%
“…CESD is a milder, later onset disorder, characterized by CE accumulation in visceral tissues; higher residual LAL activity in patients affected by CESD as compared with Wolman disease may be the basis for the milder phenotype of CESD. 28 Because efforts were concentrated on measuring candidate CEH enzymatic activity in cell-free assays, potential endocytic pathways that contribute to this process-requiring cytoskeletal integrity to transpire-were not discovered. An effective way to characterize the hydrolytic arm of the CE cycle is to incubate cells in the presence of an extracellular cholesterol acceptor and an ACAT inhibitor (to prevent cholesterol reesterification following hydrolysis), and to measure the amount of CE remaining as compared with the initial amount of cellular CE; in this way, dissipation of CE can be expressed as percentage of hydrolysis and the contribution of various enzymes/pathways to this process can be measured in a biologically relevant context, using LDs as substrate.…”
Section: Acid Lipolysismentioning
confidence: 99%